Modelling frame losses in a two hop atm network. - Tsai, Zsehong
Under the assumption that even a single cell loss could lead to a frame loss, we obtain formulas for the frame loss probability in a two hop ATM network using two discrete time queueing models: the single queue model and the tandem queue model. Our results are also found to be much more accurate than the independent cell loss estimation.
Keywords: Queueing models; Frame loss probability; ATM network